METHOD FOR PREDICTING THE DURABILITY OF ELECTRONIC EQUIPMENT - Zhadnov, V. V.; Kulygin, V. N.; Zotov, A. N. (Radio Electronics, Computer Science, Control, 2019)
Context. Constant growth of spacecraft operating life requirements leads to creating equipment which fits these requirements. From this point of view, specifically durability prediction allows to evaluate the potential of creating equipment with a long operating life. On early stages of equipment’s development analytical methods of durability prediction are used. Obviously, the more precise the estimation is, the more likely that the practical test will confirm the durability predictions. Therefore, improving the engineering techniques of the durability prediction is a relevant problem. Objective. The objective of this research is to improve the quality of design work by enhancing the engineering techniques of the durability prediction, which raise the authenticity of the evaluations. Method. Life of the equipment are calculated using the statistical modelling method (Monte-Carlo method). This method takes into consideration probabilistic characteristics of constituent elements’ life. Results. As a result, the problem of predicting operating life of electronic equipment using the reference data on early stages of development is solved. An analysis of standardized method of durability prediction was performed which revealed existing limitations for using this method when predicting operating life of electronic equipment. An alternate, statistical method of predicting operating life of electronic equipment was suggested and a software implementation was created. Developed software was tested and verified. Analytical experiments were performed to show the authenticity of the suggested method and to compare it to the standardized one. Conclusions. Thus, results of the performed research show that the standardized method is applicable only for calculating the minimum operating time. Also, it was concluded that the truncation parameter of element’s life distribution, variation coefficient of life and some specific qualities of dependability prediction scheme have to be taken into consideration when predicting durability of electronic equipment.